Deschooling Concept in Islamic Education: a Comparative Study of Ivan Illich and Ki Hajar Dewantara - Riyazati, Shushmittha; Muhid, Abdul (Universitas Muhammadiyah Ponorogo, 2024)
This research analyzes and compares Ivan Illich's concept of